1998
DOI: 10.1097/00002030-199803000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Profile of central nervous system pathology in patients with AIDS

Abstract: Patient profile and risk factors for AIDS in India differ from those reported in industrialized countries. Although not reported from India in the pre-AIDS era, toxoplasmosis was the most frequently observed CNS opportunistic infection in our study. CNS tuberculosis is frequently observed in Indian AIDS cases compared with reports from industrialized countries where its occurrence is uncommon. Death due to systemic opportunistic infections may punctuate the course of HIV encephalitis and prevent its full-blown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 13 publications
4
36
0
2
Order By: Relevance
“…However, given that they were all lost to follow-up or died, it is impossible to determine if these were true false positives or due to dual infection (TB and cryptoccocal meningitis). Indeed, our study had seven patients with both cryptococcal and TB meningitis, and dual infection is well described (37,38). There were also five patients, most with very low CD4 counts, with definite TBM who had negative RD-1 ELISOPT assays.…”
Section: Discussionmentioning
confidence: 92%
“…However, given that they were all lost to follow-up or died, it is impossible to determine if these were true false positives or due to dual infection (TB and cryptoccocal meningitis). Indeed, our study had seven patients with both cryptococcal and TB meningitis, and dual infection is well described (37,38). There were also five patients, most with very low CD4 counts, with definite TBM who had negative RD-1 ELISOPT assays.…”
Section: Discussionmentioning
confidence: 92%
“…Two autopsy studies from India on AIDS patients have also not documented even a single PCNSL case, (Lanjewar et al, 1998;Satishchandra et al, 2000) although autopsy studies in the west have demonstrated that PCNSL occurs frequently (12-40%) in patients with AIDS (Loureiro et al, 1988;Goplen et al, 1997). These facts appear paradoxical because HIV prevalence is quite high in India.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact it is not a common practice to conduct an autopsy in HIV/AIDS patients that could give the actual prevalence of AIDS-associated CT being underestimated. CT is one of the most common opportunistic infections of the CNS (Wadia et al, 2001;Nobre et al, 2003) as reported in an autopsy series conducted in India (Lanjewar et al, 1998a;Lanjewar et al, 1998b) and in other clinical settings Souza et al, 2008). The majority of AIDS-related diseases diagnosed at autopsy had not been clinically diagnosed or suspected antemortem (Eza et al, 2006).…”
Section: Neuropathology Of Toxoplasmosis: From Pre To Haart Eramentioning
confidence: 99%